Paul's political strategy in 1 Corinthians 1-4: constitution and covenant - Bitner, Bradley J. (Monograph series / Society for New Testament Studies, 2015)
Machine generated contents note: Introduction: constituting the argument; Part I. Constitution and Covenant in Corinth: 1. Paul and politics; 2. Law and life; 3. The Corinthian constitution; 4. Traces of covenant in Corinth; 5. Constituting Corinth, Paul, and the assembly; Part II. Constitution and Covenant in 1 Corinthians 1:1-4:6: 6. 1 Corinthians 1:4-9 and the politics of thanksgiving; 7. 1 Corinthians 3:5-4:5 and the politics of construction; Conclusion: comparison of constitutions